2017
DOI: 10.1002/rcm.7898
|View full text |Cite
|
Sign up to set email alerts
|

Ultra‐performance liquid chromatography/multiple reaction monitoring mass spectrometry quantification of trastuzumab in human serum by selective monitoring of a specific peptide marker from the antibody complementarity‐determining regions

Abstract: The strategy used to set up the UPLC/MRM MS methodology based on monitoring specific peptide markers within CDRs can be potentially applied to the detection and quantification of other humanized or human mAbs in biological fluids. Copyright © 2017 John Wiley & Sons, Ltd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…Recently, it has been reported that the expression of an scFv against HER2 derived from Trastuzumab (drug bank number DB00072) in SHuffle at 30 • C resulted in enhanced solubility and a higher expression level of the molecule as compared to its expression in BL21 (DE3) at 37 • C [109][110][111][112].…”
Section: Cytoplasmic Expressionmentioning
confidence: 99%
“…Recently, it has been reported that the expression of an scFv against HER2 derived from Trastuzumab (drug bank number DB00072) in SHuffle at 30 • C resulted in enhanced solubility and a higher expression level of the molecule as compared to its expression in BL21 (DE3) at 37 • C [109][110][111][112].…”
Section: Cytoplasmic Expressionmentioning
confidence: 99%
“…Essential for minimizing technical variations during sample preparation is the addition of an internal standard (IS), displaying similar or identical physical and chemical features, which allows monitoring of the full sample preparation workflow.- 10,12,14 LC-MS/MS methods using multiple reaction monitoring (MRM) for quantification of only trastuzumab in human serum have been described previously, including a method employing two surrogate peptides reaching a sensitivity of 5 μg/mL, and another reaching a sensitivity of 20 ng/mL with the latter using high resolution MS detection. [15][16][17][18] To facilitate quantification of co-administered mAbs, multiplex LC-MS/MS methods have been developed. However, until recently these assays always required specific reagents for affinity purification or specific stable isotope labeled (SIL) ISs.…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al reported that two organosulfur compounds without matched library data were inferred according to the tandem mass spectra obtained using GC/Q‐TOF . Compounds in unknown complexes can be identified via selective/multiple reaction monitoring (SRM/MRM) . SRM/MRM methods run by GC/Q‐TOF MS were shown to eliminate most non‐target detection and improve specificity and sensitivity …”
Section: Introductionmentioning
confidence: 99%
“…27 Compounds in unknown complexes can be identified via selective/multiple reaction monitoring (SRM/MRM). 31,32 SRM/MRM methods run by GC/Q-TOF MS were shown to eliminate most non-target detection and improve specificity and sensitivity. 33,34 The identification of compounds in coal using GC/MS can be disturbed by co-eluted species, 35,36 which hamper the monitoring of coal conversions like hydrodeoxygenation, hydrodenitrogenation and hydrodesulfurization.…”
mentioning
confidence: 99%